Perpustakaan dan multikulturalisme: lmplementasi pendidikan multikulturalisme di perpustakaan - Agus Rifai (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2007)
As social intitution,libraries have an important role to build a social harmony. The library was essentially an entry point to the wider culture. Library collections and its varieties in subject described not only to richness of information sources available, but also reflected to openness of the library to multi culture issues. The varieties and diversities of library's users in any kinds of ages, races, cultures, beliefs, and vocations indicated that libraries were nan-stigmatizing places. Libraries were places where people as library's users learn their culture, and other culture in the world. By library's services, users were educated to improve their understabding to people customes, etiquettes, beliefs, and other cultures in order to build social and national harmony. Key words: Libraries, pluralism, multiculturalism